An Inherent Bond: External Visual Aid Has a Minor Effect on the Rate of Co-Speech Gestures - Jarbou , Samer Omar (East European Journal of Psycholinguistics, 2020)
Traditionally, the purpose of representational co-speech gestures is to repeat or represent the semantic content of accompanying speech and so to facilitate speech comprehension. To test this belief, each of 22 participants was asked to deliver an informative speech once with the support of visual aid in the form of data-show (DS) projector slides and then to deliver the same speech without using any visual aid (NDS) in a different session; the purpose was to see if using visual aid had any significant effect on gesture rate during speech production. The theoretical framework of the study is based on findings in the Information Packaging Hypothesis, the Gesture as Simulated Action framework and relevant findings in cognitive psychology and neuroscience. The results showed that all participants used gestures during both sessions; the average number of co-speech gestures was 7.2 during the NDS and 6 during the DS sessions. This shows that using visual aid that supports the semantic content of speech did not lead to a significant reduction in the number of co-speech gestures in the DS sessions; it also indicates that the role of co-speech gestures is not merely to repeat the semantic content of accompanying speech. These results confirm previous findings in cognitive psychology that speech and accompanying gesture are cognitively and instinctively connected as one unit and that co-speech gestures possibly have an essential role in facilitating speech conceptualization and production. Speech and co-speech gestures are neurologically interconnected and they are impulsively produced whenever a speaker intends to communicate a message. These findings also add further evidence to relevant research which emphasizes that co-speech gestures are not produced merely as visual aid that aims to supplement speech.